Cardiovascular Magnetic Resonance in Early Detection of Radiation Associated Cardiotoxicity With Chest Radiation - Vallabhaneni, Srilakshmi; Wang, Yue; Zhang, Ying; Smith, Amanda; Zou, Wei; Feigenberg, Steven; Plastaras, John; Freedman, Gary; Witschey, Walter R. T.; Ky, Bonnie; Han, Yuchi (Frontiers in Cardiovascular Medicine, 2022)
Background Chest radiation therapy (RT) is known to be associated with cardiotoxicity. However, the changes in myocardial tissue characterization with radiation-induced cardiotoxicity are not well-understood. Objectives This study sought to assess the changes in left ventricular function and tissue characterization using cardiovascular magnetic resonance (CMR) in patients receiving RT. Materials and Methods Between June 2015 and July 2018, we enrolled patients with breast, lung cancer, or lymphoma with plan to receive chest radiation after chemotherapy. CMR was performed using a 1.5T scanner at baseline and 6 months after RT. Myocardial volume, function, strain analysis using feature tracking, and tissue characterization including late gadolinium enhancement (LGE), T1, T2, T1ρ (rho), and extracellular volume fraction (ECV) were measured and compared using non-parametric methods. Results The final cohort consisted of 16 patients, 11 of whom completed both baseline and follow-up CMRs. Patients were matched to 10 healthy controls. At baseline prior to RT, compared to controls, patients had lower global circumferential strain (GCS) (15.3 ± 2.2% vs.18.4 ± 2.1%, p = 0.004), and elevated T2 (47.9 ± 4.8 ms vs. 45.0 ± 1.5 ms, p = 0.04) and T1ρ values (78.4 ± 5.9 vs. 66.9 ± 4.6 ms, p < 0.001). Two patients had LGE. There was no significant difference in the average T1 values or ECV. There was a trend toward lower LV ejection fraction and global longitudinal strain (GLS). At 6-month follow-up after RT, there were no significant changes in all the CMR parameters. Conclusion At 6-month following chest radiation therapy, there was no change in LV and RV EF, LV and RV GLS, LV GCS, and myocardial tissue characterization using LGE, T1, ECV, T2, and T1ρ in a small cohort of patients. However, the baseline T2 and T1ρ were elevated and LV GCS was reduced compared to controls indicating ongoing myocardial edema and subclinical dysfunction post-chemotherapy.